Study for detection of metallic contaminant in electrode of lithium-ion battery using a Hall probe - Abdul Azim, Jais (2012)
Lithium-ion battery is commonly used for mobile power supply such as laptop and mobile telephone, because of its high energy density, but when malfunctions such as short circuit occurred inside battery, it could lead to ignition or explosion, and the battery safety is recognized as social problem. In process of battery production,metallic contaminant mix with parts of a battery can be a cause of short circuit inside battery. Therefore, it is necessary to detect at production stage. Study for detection metallic contaminant in battery using high temperature SQUID is currently in progress and by using this, 50tm ferromagnetic metal piece can be detected successfully. However, a cooling medium or cryogenic refrigerator is necessary for SQUID operation, so that the total measurement system becomes large size and expensive. On the other hand, Hall probe is known to be cheap and high versatility magnetic field sensor. Although measurement sensitivity of magnetic field for Hall probe is much lower than SQUID, by applying an external magnetic field can increase the field generated from magnetized metallic contaminant, resulting into increase for possibility to detect the metallic contaminant. In this research, we measured the magnetic field distribution of metallic contaminant in electrode for lithium-ion battery using Hall probe and examined the applicability for metallic contaminant detection technology that is more simple, easier and cheaper.